2021
DOI: 10.25133/jpssv302022.006
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Ties and Health Care: Examining the Social Networks of Filipino Migrant Domestic Workers in Hong Kong

Abstract: This paper explores the relationship between the social networks of Filipino migrant domestic workers (FMDWs) in Hong Kong and the accessibility of health resources, especially for migrant women. This study primarily draws evidence from ethnographic interviews with 20 FMDWs in Hong Kong. Likewise, this analysis also relied on field notes from participant observations during formal meetings and informal activities. This paper reveals that FMDWs strategically use their strong and weak ties in managing risks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…While considerable attention has been given to influencing factors at the macro level, little is known about how FDHs exert agency to handle workplace hazards on a day-to-day basis. Among the available studies that have examined FDHs' strategies for workplace health management, most have focused on social support, which involves engaging external sources to acquire assistance and resources (Oktavianus and Lin, 2021;Piocos et al, 2022). It is worth exploring how FDHs address abuse and exploitation using internal resources when seeking help from others is not a preferred option given their muted status.…”
Section: Structural and Cultural Underpinnings Of Abuse And Exploitationmentioning
confidence: 99%
See 2 more Smart Citations
“…While considerable attention has been given to influencing factors at the macro level, little is known about how FDHs exert agency to handle workplace hazards on a day-to-day basis. Among the available studies that have examined FDHs' strategies for workplace health management, most have focused on social support, which involves engaging external sources to acquire assistance and resources (Oktavianus and Lin, 2021;Piocos et al, 2022). It is worth exploring how FDHs address abuse and exploitation using internal resources when seeking help from others is not a preferred option given their muted status.…”
Section: Structural and Cultural Underpinnings Of Abuse And Exploitationmentioning
confidence: 99%
“…However, social support deficiency could be a problem among FDHs since most of them have migrated alone and lack strong-tie support networks consisting of family members and close friends in the host countries (Lin and Sun, 2010). Previous research indicated that FDHs seldom communicate their support needs with close kin back home because they do not want the latter to worry or offer unhelpful advice (McKay, 2007;Piocos et al, 2022). Instead, FDHs in Hong Kong may seek informational support from local community organizations, fellow migrant workers, or their employers to acquire health tips and advice on ways of accessing health services (Oktavianus and Lin, 2021;Piocos et al, 2022).…”
Section: Coping and Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Antoniades et al [ 25 ], social networks can promote migrant workers’ uptake of mental health services. Piocos III et al [ 26 ] shows that by strategically using social networks, FDWs in Hong Kong SAR of China engage in various methods to collect healthcare information and resource, and participate in conversations to improve the health-related policies of their homeland. Nevertheless, the issue of health conditions and access to healthcare among migrant domestic workers deserves more concern from the governments of origin- and receiving countries, non-government organizations, and scholars.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are studies exploring the health of foreign migrant domestics workers, these studies are highly concentrated on the traditional destinations of migrant domestic workers, such as European countries [ 9 , 13 , 30 ], Canada [ 31 , 32 ], Singapore [ 5 ], the United Kingdom [ 16 ], the United States [ 33 ], Hong Kong SAR of China [ 10 , 23 , 26 ] and Macao SAR of China [ 5 , 34 , 35 , 36 ]. Less attention has been paid to the working conditions and health issues of migrant domestic workers, especially irregular migrant domestic workers, in “new” destinations such as mainland China.…”
Section: Introductionmentioning
confidence: 99%